The Role of Policy in Building Human Resources (Case Study of the Ustadz Program of the Ustadz Boarding School Raudlatut Tholibin Batu Tunau) - Abduh, Muhamad; Yahyadin, Muhammad; Ahdar, Muhammad; Suriansyah, Ahmad; Purwanti, Ratna (Universitas Pahlawan Tuanku Tambusai, 2025)
Human resource development in the education sector is a strategic effort to improve the quality and competitiveness of education. This study analyzes educational policies related to the development program for ustadz at Pondok Pesantren Raudlatut Tholibin, Batu Tunau Village, using a qualitative approach and case study method. The findings reveal that the ustadz development program—covering pedagogical training, enhancement of religious competence, and character building—significantly contributes to the quality of teaching and student character formation. The policy also strengthens the role of pesantren in producing excellent human resources grounded in Islamic values. Furthermore, the evaluation and implementation of the program are conducted in a more efficient and objective manner, promoting sustainable improvement. This study recommends strengthening education policies based on local needs and fostering synergy among the government, pesantren, and community in supporting educational human resource development.